Meningkatkan kemampuan komunikasi dan kepercayaan diri siswa melalui program CERIA cerita anak di kelas IV - Subanindro Subanindro (Persatuan Guru Republik Indonesia Kota Banjarbaru, 2022)
Students' communication skills and self-confidence can be improved through the CERIA Stories for Children program. This program is routinely run before the first lesson starts for about 10 to 15 minutes. The students get a turn as storytellers in front of the class according to the schedule they have made themselves. The theme is chosen according to the student's choice or preference. Story material can be made yourself or based on story books that have been read from home. How to convey the story can be directly without looking at the reading. However, if there are students who still have difficulty in delivering, they can use the results of the image on a paper. The teacher who is escorting the class can help dig by asking what students are reading. It is believed that in the long run, if this program is run with discipline, it can have an impact on student communication and confidence.